THE ROLE OF NON-FORMAL AND INFORMAL EDUCATIONIN THE DEVELOPMENT OF THE TERRITORIES OF SOUTHERN UKRAINE ON THE BASIS OF SMART – SPECIALIZATION - SAVINA, HALYNA; SAVIN, STANISLAV; DYAGILEVA, ELENA; MAKARCHUK, DARYNA; SOKUR, II (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the essence and prerequisites for the formation and application of informal and non-formal education in Ukraine. The essence of formal education is revealed and distinctive features of informal and non-formal education are determined, namely: absence of age restrictions; lack of time frame; lack of preconditions for starting training (level of preliminary training, etc.); short training time (several days, several weeks); accessibility for residents of small towns; the possibility of using distance learning; the possibility of flexible formation and updating of training programs for the needs of the local community. The connection between human capital and informal and non-formal education is shown. The expediency of studying the development of territories from the standpoint of the concept of SMART-specialization is substantiated. SMART-specialization involves identifying the strengths and development of the region's competitive advantages and determining the direction of strategic development related to the priority resources of the region. Examples of resource specialization of the territories of the South of Ukraine are given. Particular attention is paid to resources used in tourism. It is noted that territorial tourist and recreational resources are distributed very unevenly. Areas located on the coast are more attractive to tourists during the summer holidays, while areas away from the coast can offer year-round tourism products that are based on the use of such resources as: cultural, architectural, health -recreational, event-cognitive and others. The role of formal and non-formal education in the development of the territories of the South of Ukraine is determined on the basis of SMART - specialization, which is as follows: informal and non-formal education increase the level of knowledge of the population in the context of effective ecological and economic use of local resources. This means the following: first, it is necessary to study the priority of territorial resources in terms of obtaining at their expense environmental, economic and social effects; secondly, it is necessary to plan programs of informal and non-formal education in a certain territory, based on how progressive the changes will be due to the acquired knowledge about the use of local resources.
Keywords: formal; informal and non-formal education; development of territories; SMART-specialization; priority resources of the region; sphere of tourism